ISLAM NUSANTARA: SEBUAH ARGUMENTASI BERAGAMA DALAM BINGKAI KULTURAL - Hanum Jazimah Puji Astuti (IAIN Salatiga, 2017)
The emergence of Islam Nusantara is the typical of Indonesia, where Islam Nusantara is declared as a universal religion, manifested in its teachings including religious law (fiqh), trust (faith), and the ethical (the moral). Although Islam Nusantara gives a new ambience in Islam by assimilating a culture into religion, this method is not contagious to the purity of Islamic teachings by taking Quran and Hadith as the guidances and directions in the Indonesian social life. Islam teaches mutual respect and reciprocal tolerance. This religion teaches the adherents to love others, to mercy and nurture regardless of race, nationality, and social structure. This is in line with the Indonesian Islam commonly called ‘Islam Nusantara’. It can be said that someone who lived in the religion, including people that comprehend the religion intrinsically, occupies religion as a guide of life, applies and practices based on the belief. At the social level, religious values serve as the basis for adopting a life policy. AbstrakPemunculan Islam Nusantara merupakan ciri khas Indonesia, di mana Islam Nusantara ini di nyatakan sebagai agama yang universal, dimanifestasikan dalam ajarannya, yang mencakup hukum agama (fiqh), kepercayaan (tauhid), serta etika (akhlak). Meskipun Islam Nusantara memberikan nuansa baru dalam beragama Islam dengan memasukkan budaya dalam agamanya, namun cara beragama seperti ini tidak menghilangkan kemurnian ajaran Islam itu sendiri, dengan menjadikan al Quran dan Hadits sebagai pedoman dan tuntunan dalam kehidupan sosial masyarakat Indonesia. Dalam beragama, Islam mengajarkan untuk saling menghargai dan saling toleransi, agama yang mengajarkan penganutnya untuk saling menyayangi, mengasihi dan mengayomi tanpa me mandang ras, kebangsaan, serta struktur sosial. Hal ini sejalan dengan Islamnya Indonesia yang biasa disebut ‘Islam Nusantara’. Dapat dikatakan seseorang yang menjalani agama itu, termasuk orang yang menghayati agamanya dengan cara intrinsik, agama dijadikan sebagai pedoman hidup, dijalankan dan diamalkan sesuai dengan keyakinannya. Pada tataran sosial nilai-nilai agama dijadikan sebagai dasar dalam mengambil kebijakan hidup.